Chuck. The complete second season [videorecording (DVD)] - Levi, Zachary, 1980-; Strahovski, Yvonne, 1982-; Gomez, Joshua, 1975-; McPartlin, Ryan, 1975-; Lawrence, Mark Christopher, 1964-; Sahay, Vik; Krinsky, Scott, 1968-; Ling, Julia, 1983-; Lancaster, Sarah, 1980-; Baldwin, Adam, 1962-; Schwartz, Josh, 1976-; Fedak, Chris; et al. (Distributed by Warner Home Video, 2009)
Chuck is in luck. Intersect II is ready for the espionage service. That means that the old Intersect, a.k.a. Chuck, can go back to his old life. But if Chuck goes, he's going to be gone. Casey has orders to off him. Chuck survives to unravel mysteries of the past, become a hero in the present, and chop-and-drop himself into an even more perilous future.